The effect of nearby obstacles in surface condensations on external thermal insulation composite systems: Experimental and numerical study - Eva Barreira (2014)
External thermal insulation composite systems are, nowadays, quite common in European buildings, used both in new constructions and refurbishment. Unfortunately, external thermal insulation composite systems can have serious problems of biological growth causing the cladding defacement. Studies carried out in recent years allowed understanding the hygrothermal behaviour of external thermal insulation composite systems. It is known that biological growth is due to high values of surface moisture content, which depends mostly on exterior surface condensation. Despite this existing knowledge, there is little information available about the influence of obstacles near the facade on condensation and surface moisture content. In this article, the results of a field test campaign to assess the influence of obstacles on surface condensation are presented. They show that nearby obstacles influence exterior surface temperature during the night and, consequently, surface condensation. Different obstacle configurations have different effects, which may lead to stained patterns on the facade due to differential biological growth rates. The effect of nearby obstacles on exterior surface condensation, revealed during the test campaign, addressed the development of a numerical routine to simulate their influence. This routine can be used with any existing hygrothermal model with the ability to simulate explicitly the radiative balance on the exterior surface. It calculates the increase in long-wave radiation due to the obstacle as a function of its geometry and emissivity of its surface. This extra amount of radiation is added to the atmospheric radiation that is an input of the hygrothermal models. The validation of this routine was performed by comparing simulated and experimental results. An example of the practical use of this routine is also presented in this article, with the calculation of the exterior surface condensation on different facades covered with external thermal insulation composite systems, with and without nearby obstacles, and its comparison with the coating defacement that they actually present.